2020
DOI: 10.1136/emermed-2020-210125
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of point-of-care lung ultrasound in COVID-19

Abstract: BackgroundA promising modality for diagnosing pulmonary manifestations of COVID-19 in the emergency department (ED) is point-of-care ultrasound (POCUS) of the lungs. The currently used PCR as well as chest X-ray and CT scanning have important disadvantages. The aim of this study is to evaluate the diagnostic accuracy of POCUS in patients with suspected pulmonary manifestations of COVID-19 in the ED.MethodsThis prospective diagnostic accuracy study was conducted at the ED of our non-academic level 1 trauma cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 20 publications
4
56
0
2
Order By: Relevance
“…In the current study, almost all patients with lung abnormalities on the chest CT scan were correctly classified as positive by LUS, showing its reliability for case identification. This corresponds with the current results of the literature, which reports a very high sensitivity (89-100%) for the diagnosis of COVID-19[ [29] , [30] , [31] ].…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, almost all patients with lung abnormalities on the chest CT scan were correctly classified as positive by LUS, showing its reliability for case identification. This corresponds with the current results of the literature, which reports a very high sensitivity (89-100%) for the diagnosis of COVID-19[ [29] , [30] , [31] ].…”
Section: Discussionsupporting
confidence: 91%
“…Although our study did not evaluate the diagnostic performance of lung ultrasound, lung ultrasounds have been previously studied for diagnosing and evaluating the clinical course of patients with COVID-19. A prior study reported that point-of-care lung ultrasound had a sensitivity of 89% and specificity of 59% [24]. Even though there is no known pathognomic ultrasound finding for COVID-19, ultrasound can detect pulmonary dynamics for patients with COVID-19 [25].…”
Section: Discussionmentioning
confidence: 99%
“…LUS is a low-cost imaging technique that is quick to perform and repeat at the bedside by emergency physicians, intensivists, or cardiologists (point-of-care (POC) LUS). This technique allows a dynamic study of the lung without ionizing radiation exposure and with a reduced overall nosocomial transmission risk, also useful in vulnerable groups such as children and pregnant women [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. LUS can detect bilateral, subpleural, mainly posterobasal interstitial–alveolar damage in COVID-19 pneumonia with the appearance of thickening/irregularity of the pleural line, increased B lines to different degrees of extension with focal pleural B lines in the early stage of the disease, and multiple coalescent B lines (white lung) in critically ill patients [ 53 , 54 , 56 ].…”
Section: Lung Ultrasoundmentioning
confidence: 99%
“…However, LUS cannot accurately detect the presence of air bronchogram as well as pneumothorax [ 57 , 58 ]. Some authors have noted that LUS may have a potential role in EDs for triaging symptomatic patients, managing ventilation, weaning ICU patients, and monitoring COVID-19 pneumonia and its evolution toward ARDS in critically ill patients [ 49 , 50 , 51 , 55 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. A focused cardiac ultrasound study (FoCUS) performed at the bedside can also be useful in COVID-19 patients with cardiac events [ 64 ].…”
Section: Lung Ultrasoundmentioning
confidence: 99%